Pelatihan Shodou bagi Guru-Guru MGMP Bahasa Jepang di Sumatera Barat - Idrus Idrus; Darni Enzimar Putri; Imelda Indah Lestari; Lady Diana Yusri (Warta Pengabdian Andalas, 2019)
Shodou is a traditional art form in writing kanji characters expressively and creatively. Japanese writing often used to practice Shodou is Kanji, which cannot separate from Japanese. In learning Japanese, we can used Shodou as a way to improve the ability of students, especially vocabulary mastery through Kanji writing. Therefore, Shodou needs to be mastered by Japanese language teachers. Shodou's training conducted by using lecture and training methods for Japanese MGMP teachers of senior high school in West Sumatra. The trainees were enthusiastic about participating in this Shodou training because they also gained knowledge about the benefits of Shodou in learning Japanese. The benefits of Shodou in learning Japanese include increasing patience, increasing concentration, increasing harmony, and improving memory.